FWCSCMR: Scalable Fuzzy Weighted Clonal Selection Clustering based on MapReduce for microarray gene expression - et al., Vishal Goyal (International Journal of Control and Automation, 2019)
Data clustering may be a terribly helpful data processing technique to seek out teams of comparable objects gift within dataset. In any clustering method, validation of results of clustering, lustiness to intrinsic outlier knowledge and handling of large amount of data are most commonly known difficulties. In order to rectify these difficulties, a fuzzy weighted clustering approach is proposed in this research. But the optimization of weights in clustering approach becomes terribly troublesome task for organic phenomenon knowledge.